Peculiarities of employee professional development in the world, European Union and Latvia - Valdis Jukšs (Insights into Regional Development)
Within this study, employee professional development is conceptually understood as a component of lifelong learning. The concepts of lifelong learning, a learning society and even a learning economy are popular and theoretically justified as necessary prerequisites for the competitiveness and the economic performance of countries in the modern world. The problem is that Latvia (like most countries with low economic performance) is still not a learning society – especially compared to the countries of the European Union. In this regard, it became necessary to empirically measure the economic importance of employee professional development in the modern world in order to justify the management of lifelong learning based on the economic paradigm. For an empirical interpretation of lifelong learning and employee professional development, the author used the Global Talent Competitiveness Index (GTCI) and indicators of the economic performance of the world’s countries for the period from 2018 to 2020. Applying four methods of quantitative data analysis – correlation analysis, regression analysis, comparison of means and discriminant analysis, the author proved the following: in the modern world, employee development is mainly a factor, but also an indicator of competitiveness and economic performance of countries, since significant investments are required to implement employee professional development. Nevertheless, the sustainable management of lifelong learning and the self-motivation of employees helps to create a learning society not only based on material investment, but also through the development of a learning culture.